Review on Hybrid Solar Air Heater - C.B. Saxena (AG Volumes, 2021)
The primary component of a solar energy usage system is a solar air heater (SAH). Thermal energy is generated at the absorbing surface of this kind of air heater, which is subsequently transferred to a fluid running through the collector. Because of their intrinsic simplicity, SAHs are the most often utilised collecting devices at a low cost. When it comes to solar-heated air systems, there are three main uses: heating buildings and drying wood and agricultural crops. For example, solar energy may be used for a variety of purposes including generating electricity, heating or cooling a building's interior area, powering air conditioners and heat pumps, and generating chilled water for industrial processes. Due to their versatility and ability to provide considerable environmental advantages, solar energy systems should be used wherever feasible.